MANAGEMENT OF HUMAN RESOURCES IN CONDITIONS OF INNOVATION DEVELOPMENT - Irina Savchenko; Svetlana Nedvizhay (Вестник Северо-Кавказского федерального университета, 2022)
This article investigates the current management issues of management of human resources as a fundamental factor for economic growth and defining category for achievement of competitive advantages of modern social economic systems, an innovative type of modern production, which formulates the problem of professional success and defines special system of selection, retraining and social adaptation of workers.